Estudo do desempenho de um alimentador de sólidos tipo válvula-L de pequeno diâmetro - Feltran, Marina de Barros (2005)
A controlled and uniform solids feeding in process equipment is important for a good performance operation, and distinct work conditions may be obtained depending on the feeding systems characteristics. In this work, a solids feeding system was studied aiming to have its performance characterized and analyzed. The solids feeder is a non-mechanical valve known as L-valve. The experimental apparatus used in this study is composed by an acrylic L-valve with a 23 mm inner diameter and a vertical pneumatic conveying line, made of stainless steel with 23 mm inner diameter and 1,90 m length. The equipment have altogether 18 pressure taps distributed along of it, two orificeplate flow meters to measure the air flow rates and the aeration flow rates, and a sample collector to measure the solids flow rates. In this work were used glass spheres with average diameters ranging from 260 µm to 1 mm. The measurements of solids flow rates, air flow rates, and pressure profiles allowed the solids feeder characterization and the analysis of its performance in conveying operation. The runs accomplished with the L-valve operating isolatedly showed different flow patterns depending on aeration flow rate range and indicated that the particle diameter influences the minimum aeration flow rate required to conveying. The runs with L-valve operating in pneumatic conveying line showed the same tendencies of solids flow rates and pressure drops in L-valve that those obtained in L-valve characterization runs. The operation with 23 mm diameter inner L-valve was more efficient for smaller diameter particles.